Pediatric Emergency Department Return: A Literature Review of Risk Factors and Interventions. Issue 8 (August 2016) - Tran, Quincy Khoi; Bayram, Jamil D.; Boonyasai, Romsai T.; Case, Meredith A.; Connor, Christine; Doggett, David; Fawole, Oluwakemi A.; Ijagbemi, O. Mayowa; Levin, Scott; Wu, Albert W.; Pham, Julius Cuong
Abstract : Background and Objective: Children discharged from emergency departments (EDs) are often at risk for ED return. The objective was to identify risk factors and interventions to mitigate or prevent ED return among this patient population. Methods: Structured literature review of PubMed and clinicaltrials.gov was conducted to identify relevant studies. Inclusion criteria were studies evaluating ED returns by identifying risk factors and interventions in the pediatric population. Emergency department return was defined as returning to the ED within 1 year after initial visit. Abstract and full text articles were reviewed, and data were abstracted by 2 independent authors. Results: A total of 963 articles were screened and yielded 42 potential relevant articles involving pediatric population. After full text review, a total of 12 articles were included in the final analysis (6 on risk factors and 6 on interventions). Risk factors for pediatric ED return included behavioral/psychiatric problems, younger age, acuity of illness, medical history of asthma, and social factors. Interventions included computer-generated instructions, postdischarge telephone coaching, ED-made appointments, case management, and home environment intervention. Emergency department–made appointments and postdischarge telephone coaching plus monetary incentive improved outpatient follow-up rate but not ED return. Home environment assessment coupled with case management reduced ED returns specifically among asthma patients. Conclusions: Several patient and visit characteristics can help predict children at risk for ED return. Although some interventions are successful at improving postdischarge follow-up, most did not reduce ED returns.